Subcutaneous administration of isatuximab in patients with multiple myeloma by an on-body delivery system: results of a nurse survey - Sánchez Avello, Nuria; Calvo Pajares, Paula; Cordero, Paul; Suzan, Florence; Barlas, Connie (Frontiers in Oncology, 2025)
IntroductionSubcutaneous (SC) administration of the anti-CD38 antibody isatuximab (Isa) by an on-body delivery system (OBDS), plus pomalidomide-dexamethasone, has demonstrated safety and efficacy comparable to intravenous (IV) administration, with no infusion reactions and excellent local tolerability in multiple myeloma (MM) patients. We report here results of a nurse survey designed to evaluate convenience of treatment with SC Isa, via OBDS, for healthcare providers and MM patients.MethodsA newly developed, expert-vetted questionnaire was used to survey nurses with experience in SC administration to MM patients enrolled in clinical trials. Results on extent of agreement with pre-vetted statements were expressed as percentages of respondents. Free-text answers were analyzed for each respondent and grouped by topic.ResultsAll surveyed nurses (N=12) agreed that OBDS administration improved efficiency and was easy to learn and administer with a low level of physical burden, leading to a preference for OBDS over IV Isa administration and facilitating a positive treatment experience for the patients. Compared with IV dosing, the OBDS improved patient comfort and could reduce time spent in the clinic. As agreed by most nurses, main advantages for patients included no needle visibility, short treatment duration, and a generally well-tolerated and painless SC injection.ConclusionsOur findings show a high level of confidence among nurses in SC Isa administration via OBDS, due to the ease of use, tolerability, and time savings achieved with hands-free OBDS injections. Our findings suggest applicability of the OBDS for convenient SC Isa administration to MM patients in routine clinical practice.